(untitled) (Scientific journal of the Fergana State University, 2024)
In-depth study of the concept of hyponymy and hyperonymy in animal names is important for accurate classification of these animal names and their use in communication. In this article, the phenomena of hyponymy and hyperonymy, its study in world and Uzbek linguistics, as well as the hyponymic and hyperonymic features of the names of wild animals in English and Uzbek languages are analyzed. By studying the hierarchical structure of these linguistic concepts, we can further explore the relationships and categorization of wild animal names in this specific domain.